Evaluasi Kesuksesan Sistem Informasi Pelaporan dan Monitoring Kota Layak Anak dengan Model Design-Reality Gap - Kursehi Falgenti; Atikah Mardi; Ana Ruemardiana (UM Purwokerto Press, 2021)
The Child-Friendly City web-based reporting and monitoring information system was implemented at the end of 2018 in Depok City. Through the web address, http://kla.depok.id Child-Friendly City cadres could report activities of child-friendly city forums based on five clusters and 29 indicators. The public could find information on Depok City as well as a child-friendly city. After three years of implementation, evaluation was necessary to ensure that the information system operates according to the initial design. This study aimed to evaluate the success of the monitoring and reporting information system for the Child-Friendly City of Depok. The evaluation was done by looking at the gap between the initial design of the system and the reality of the system's current state. The evaluation method was a gap analysis using a design-reality gap model consisting of 7 dimensions of Information, Technology, Process, Goals and Values, Staff placement and skills, management systems and structures, and other resources (ITPOSMO). The evaluation results showed that the information system failed partially. A recommendation for improvement was proposed so that Child-Friendly Cities' reporting and monitoring information system does not fail miserably. This recommendation aimed to make the reporting and monitoring process for the child-friendly city of Depok more effective.